2002
DOI: 10.1074/jbc.m110784200
|View full text |Cite
|
Sign up to set email alerts
|

Barbiturase, a Novel Zinc-containing Amidohydrolase Involved in Oxidative Pyrimidine Metabolism

Abstract: Barbiturase, which catalyzes the reversible amidohydrolysis of barbituric acid to ureidomalonic acid in the second step of oxidative pyrimidine degradation, was purified to homogeneity from Rhodococcus erythropolis JCM 3132. The characteristics and gene organization of barbiturase suggested that it is a novel zinc-containing amidohydrolase that should be grouped into a new family of the amidohydrolases superfamily. The amino acid sequence of barbiturase exhibited 48% identity with that of herbicide atrazine-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 47 publications
1
50
0
Order By: Relevance
“…In both the reductive and oxidative pathways for pyrimidine catabolism described previously (22,48,52) the N-3-C-4 bond is cleaved hydrolytically after the C-5-C-6 double bond has been altered to decrease the aromaticity of the ring (Fig. 1).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In both the reductive and oxidative pathways for pyrimidine catabolism described previously (22,48,52) the N-3-C-4 bond is cleaved hydrolytically after the C-5-C-6 double bond has been altered to decrease the aromaticity of the ring (Fig. 1).…”
Section: Discussionmentioning
confidence: 90%
“…Comparison of Rut pathway products (E. coli K-12) to those of other pyrimidine catabolic pathways. (A) The Rut pathway, which has been studied only in vivo in E. coli K-12 (31); (B) known reductive (52) and oxidative (22,28,48) pathways for catabolism of pyrimidine rings (upper and lower pathways, respectively). Although the enzyme that initiates the oxidative pathway was originally called uracil oxidase, it is a classical monooxygenase (28).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AtzD and TrzD were identified as being homologous, but they were not connected to any other proteins or protein families in those studies (12,20,26). Barbiturase was first purified to homogeneity from Rhodococcus erythropolis JCM3132 and shown to catalyze the hydrolytic opening of barbituric acid, an intermediate in the oxidative pyrimidine catabolic pathway (34,35). Those studies reported that barbiturase was homologous to AtzD and TrzD (34,35).…”
mentioning
confidence: 98%
“…Barbiturase was first purified to homogeneity from Rhodococcus erythropolis JCM3132 and shown to catalyze the hydrolytic opening of barbituric acid, an intermediate in the oxidative pyrimidine catabolic pathway (34,35). Those studies reported that barbiturase was homologous to AtzD and TrzD (34,35). One of the reports found zinc to be present in the enzyme preparations and thus proposed that barbiturase was homologous to members of the amidohydrolase superfamily (35).…”
mentioning
confidence: 99%